Young and Malay growing up in multicultural Malaysia - Ooi, Kee Beng; Wan Hamidi Hamid (Gerakbudaya Enterprise, 2015)
In this collection of essays edited by Ooi Kee Beng and Wan Hamidi Hamid, nine young writers - Haris Zuan, Wan Hamidi Hamid, Zairil Khir Johari, Dyana Sofya Mohd Daud, Altaf Deviyati, Izmil Amri, Syukri Shairi, Raja Ahmad Iskandar and Edry Faizal Eddy Yusof - share their individual memories about growing up in Malaysia, and in some cases debate the racial politics in which they - and all Malaysians - seem inextricably caught.